Pathogenesis of the Novel Autoimmune-Associated Long-QT Syndrome. Issue 4 (28th July 2015) - Yue, Yuankun; Castrichini, Monica; Srivastava, Ujala; Fabris, Frank; Shah, Krupa; Li, Zhiqiang; Qu, Yongxia; El-Sherif, Nabil; Zhou, Zhengfeng; January, Craig; Hussain, M. Mahmood; Jiang, Xian-Cheng; et al.
<x xml:space="preserve">Abstract</x> Background— Emerging clinical evidence demonstrates high prevalence of QTc prolongation and complex ventricular arrhythmias in patients with anti-Ro antibody (anti-Ro Ab)–positive autoimmune diseases. We tested the hypothesis that anti-Ro Abs target the HERG (human ether-a-go-go–related gene) K+ channel, which conducts the rapidly activating delayed K+ current, IKr, thereby causing delayed repolarization seen as QT interval prolongation on the ECG. Methods and Results— Anti-Ro Ab–positive sera, purified IgG, and affinity-purified anti-52kDa Ro Abs from patients with autoimmune diseases and QTc prolongation were tested on IKr using HEK293 cells expressing HERG channel and native cardiac myocytes. Electrophysiological and biochemical data demonstrate that anti-Ro Abs inhibit IKr to prolong action potential duration by directly binding to the HERG channel protein. The 52-kDa Ro antigen–immunized guinea pigs showed QTc prolongation on ECG after developing high titers of anti-Ro Abs, which inhibited native IKr and cross-reacted with guinea pig ERG channel. Conclusions— The data establish that anti-Ro Abs from patients with autoimmune diseases inhibit IKr by cross-reacting with the HERG channel likely at the pore region where homology between anti–52-kDa Ro antigen and HERG channel is present. The animal model of autoimmune-associated QTc prolongation is the first to provide strong evidence for a pathogenic role of anti-Ro Abs in the development of QTc prolongation. It is proposed that adult patients with anti-Ro Abs may benefit from routine ECG screening and that those with QTc prolongation should receive counseling about drugs that may increase the risk for life-threatening arrhythmias.